Memoirs of Vladimir Lvovich Wagin - V.V. Khlebovich (Учёные записки Казанского университета: Серия Естественные науки, 2017)
This paper is devoted to Vladimir Lvovich Wagin (1907–1984), a famous parasitologist and hydrobiologist. Based on his own memories, the author emphasizes the paternal style of his relationship with students of the Biological Faculty of Leningrad University during the late 1940s – early 1950s, as well as some wonderful traits of his personality. Despite the age difference, the author and V.L. Wagin had a good friendship. The author became an invertebrate zoologist thanks to V.L. Wagin and has been holding true to his ideals for more than 60 years. According to the author's opinion, zoology is always interrelated with organismic physiology, which was inculcated by V.L. Wagin's wise advice. In order to better understand the personality of the researcher, the situation at the Department of Invertebrate Zoology of Leningrad University during the early 1950s, where V.L. Wagin worked, and some traits concerning the portrait of V.A. Dogiel who headed it are briefly described. V.L. Wagin distinguished from other professors of the department because of his reverent and very kind paternal attitude to students. He found strength for talking about science and learning, as well as life. The author especially appreciated this attitude many years later. The basis of educating zoologists at the department during that time was intense practical training in invertebrate zoology. Only a few students, including V.L. Wagin, managed to get through it. In 1957, he became the head of the Department of Invertebrate Zoology of Kazan University and modified the process of educating future zoologists, i.e., he introduced the obligatory marine practice, which, in its turn, formed a solid foundation for the development of studies in the sphere of marine biology. Thus, he laid the foundation of the Russian-known “population” of Kazan seamen, zoologists and hydrobiologists.